KONFIGURASI DAN TRANSFORMASI KEHIDUPAN BERAGAMA GENERASI MUDA PEDESAAN Studi Kasus Generasi Muda Desa Pakiskembar Kecamatan Pakis Kabupaten Malang Jawa Timur - Abdul Mubarok (Balai Penelitian dan Pengembangan Agama Semarang, 2008)
This research aimed at describing a change in the religious life of younggeneration of Pakiskembar Village, Pakis Sub district, Malang Regency, East Java, because of the influence of electrical technologyintroduced into village. The description comprised a change in the formof a variety of beliefs, a change in the religious service aspect, and achange in social aspect. The finding of this research was electricity introduced into the villagebrought specific changes into the religious life of young generation. Achange in the belief aspect tended towards irrational belief whichincreasingly reduced, which meant rasional though increasingly rose. A part of change in religious service aspect tended toward a rise, andanother part tended towards a reduction. Activities of reciting Al-Qur 'anat home underwent a change toward a reduction. Activities of recitingAl-Qur'an at the mosque/musala in month of Ramadan did not change.Participation in taraveeh and tadarus Al-Qur 'an in the month ofRamadan rose. Activities of performing congregational prayers atmosque/musala reduced. Activities of Friday prayer, Eid-ul-Fitr prayer,and janaza (funeral) prayer did not change. Changes in the social aspect were various enough. Within the socialrelegious group/organization in the village level, a rise in the numberof members occurred; participation of the young generation in thisactivity rose. Relegious education institution and the participation ofyoung generation of the young generation in this institution did not change. Various kinds of activities of PHBI rose and participation ofthe young generation also increasingly rose. The habit of talking toolder people changed, namely after electricity introduced into the village the young generation seemed not familiar enough with older people,that they lacked of respect for older people, and there was impressionthat they preferred to use Indonesian language, wich meant they startedto leave behind their local vernacular which was full of ethics of personality or of good manner towards older people. There was a changein dressing. although it was still normal, they still dressed in Moslem dress.